Toxicity of Peracetic Acid to Fish: Variation among Species and Impact of Water Chemistry. Issue 4 (20th October 2017) - Straus, David L.; Meinelt, Thomas; Liu, Dibo; Pedersen, Lars‐Flemming
Abstract: There has been strong interest in the use of peracetic acid (PAA) in aquaculture as it can be used to disinfect water and hard surfaces and thereby eliminate or lower the burden of fish pathogens. Unfortunately, there has been little research on the toxicity of PAA to fish. Twelve species of fingerling fish that are important to aquaculture were exposed to PAA for 24 h in static toxicity bioassays in well water. These fish were: fathead minnow, Pimephales promelas ; black‐nose crappie, Pomoxis nigromaculatus ; bluegill, Lepomis macrochirus ; blue tilapia, Oreochromis aureus ; channel catfish, Ictalurus punctatus ; golden shiner, Notemigonus crysoleucas ; goldfish, Carassius auratus ; grass carp, Ctenopharyngodon idella ; largemouth bass, Micropterus salmoides ; rainbow trout, Oncorhynchus mykiss ; sunshine bass, Morone chrysops × M. saxatilis ; and walleye, Sander vitreus . Median lethal concentration (LC50 ) values were estimated with the trimmed Spearman–Karber method using nominal PAA concentrations. The mean 24‐h LC50 values ranged from 2.8 to 9.3 mg/L PAA. Fathead minnow were very sensitive and blue tilapia were very tolerant to PAA exposure; LC50 values of other species tested were within the range of 4.1–6.2 mg/L PAA. More importantly, the 24‐h no‐observed‐effect concentration (NOEC) ranged from 1.9 to 5.8 mg/L PAA; the NOEC would be considered as the safe range for culturists to investigate the use of PAA. Decreased alkalinity/hardness increased the toxicity of PAA, while a small increase of dissolved organic content had no effect on PAA toxicity. Results of the present study are important information on the safe application of PAA for the aquaculture industry.